2018
DOI: 10.1016/j.hpb.2018.06.1922
|View full text |Cite
|
Sign up to set email alerts
|

Improving the efficacy of drainage for infected pancreatic necrosis by enzymatic accelerated liquefaction

Abstract: patients with the first attack of AP is still a huge clinical challenge. We aim to elucidate risk factors for the RAP and progression to CP. Methods: Medical records of patients with the first attack of AP between 2007 and 2016 were retrospectively reviewed. Total of 60 patients with RAP and randomly selected 120 patients with single episode AP were included. Results: On the comparison between single episode AP and RAP, younger age(42.8AE11.9 vs 57.6AE17.2), male(76.7 vs 56.7%), alcohol(88.3 vs 55.0%), smoking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Traditionally, surgical incision and drainage (I&D) have been the standard approach. However, there has been a shift towards minimally invasive techniques, such as percutaneous suction drain placement and aspiration of the abscess, reflecting evolving surgical philosophies (6). Previous studies have reported varying recurrence rates following different treatment modalities for breast abscess.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, surgical incision and drainage (I&D) have been the standard approach. However, there has been a shift towards minimally invasive techniques, such as percutaneous suction drain placement and aspiration of the abscess, reflecting evolving surgical philosophies (6). Previous studies have reported varying recurrence rates following different treatment modalities for breast abscess.…”
Section: Introductionmentioning
confidence: 99%